VD_FINDINFO HC / 2013 / 261 vom 5. April 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE, REVENU, REVENU HYPOTHÉTIQUE, BONUS, ENFANT, CALCUL | 179 al. 1 CC, 179 CC, 285 al. 1 CC, 285 CC